Relationship between body mass index and body condition score in Pelibuey ewes - Salazar-Cuytun, Eufracia de R.; Chay-Canul, Alfonso J.; Ptácek, Martin; García-Herrera, Ricardo A.; Rivera-Alegría, Flor de María; Aguilar-Caballero, Armando J.; Sarmiento-Franco, Luis A. (Ecosistemas y Recursos Agropecuarios, 2020)
The objectives of this study were to detect the relationship between body mass index (BMI) and body condition score (BCS) in Pelibuey ewes to predict BMI based on well-known BCS estimation. The body weight (BW), withers height, (WH), body length (BL) and BCS were determined in 402 ewes. The BMI was calculated as: BMI = (BW (kg)/WH (m)/ BL (m))/10. Relationships were estimated by means of regression models using PROC REG of the SAS. The BMI and the BCS showed a high relationship; correlation coefficient (r) of 0.80 (P<0.001). The linear regression for BMI prediction was as followed: BMI (kg/m2) = 8.38 (±0.189***) + 1.70 (±0.064***) × BCS (R2 = 0.65, MSE: 2.56; RMSE: 1.60; P <.0001 and n = 402). The BMI could be used as an indicator of the degree of obesity in non-pregnant and non-lactating Pelibuey ewes under field conditions.